Financial Performance of Islamic Commercial Banks Through Efficiency Levels and Non-Performing Financing Before and During The Covid-19 Pandemic - Afkar, Taudlikhul; Hariawan, Ferry; Fauziyah, Fauziyah; Shera, Shinta Clarita Dwi (Monex: Journal of Accounting Research, 2024)
The real sector and the financial sector have been affected by the Covid-19 pandemic for approximately 2 years. It condition makes the banking financial sector pay attention to the level of operational expenses efficiency and be careful in channeling financing in order to reduce the occurrence of bad financing caused by defaults from customers. Analysis of the capabilities of Islamic banks in Indonesia in terms of operational cost efficiency and managing problematic financing in conditions before and during the Covid-19 pandemic so that the ability of Islamic banks to manage their financial performance will be known is the aim of this research. Saturated sampling was the technique for sampling this research from the research population of 14 Islamic commercial banks in Indonesia. Documentation is used as a technique in collecting data from the combined financial reports of 14 Islamic commercial banks. Data before the pandemic can be seen from the 2018-2019 financial reports, while 2020-2021 data during the pandemic. Paired sample t-test with Jamovi media was used as a data analysis technique. The findings of this research show that during the Covid-19 pandemic, the level of efficiency and non-performing financing of Islamic banks has decreased, meaning that the financial performance of Islamic banks is better and operating costs are more efficient, problem financing is reduced, so that the potential for increased profitability is higher. Keywords: operating expenses and operational income, non-performing financing, financial performance, Islamic banking, covid-19.